Occurrence of Canine Mammary Tumours in Wayanad District, Kerala - Tamilvani, P; Anoopraj, R; Ajith Jacob George; Pradeep, M; Muhasin Asaf, V. N; Hamza Palekkodan; Dhanush Krishna, B; Athira P. Nair (The Indian Veterinary Journal, 2024)
The present report details the occurrence of canine mammary tumours presented at Teaching Veterinary Clinical Complex, Pookode during a period of one year.Among the 22 proliferative growths from the mammary region studied, the number of hyperplastic proliferation and malignant neoplasms was one and 21, respectively. Most of the female dogs (90.9%) with mammary tumours were sexually intact. The highest occurrence of tumours was observed in the age group between 9 to 12 years (54.55%). Nearly, three-fourth (72.73%) of mammary tumours were observed in pure-bred dogs.  Grossly, canine mammary tumours exhibited a diverse range of external appearances regarding shape, size, colour and consistency. Single as well as multiple gland involvements were noticed. Glands of the caudal region, particularly the inguinal (36.36%) and caudal abdominal gland (22.73%) were more frequently affected. Histotypes of malignant tumours in descending frequency of occurrence were carcinoma-malignant myoepithelioma, tubulopapillary carcinoma, carcinosarcoma, carcinoma arising from benign mixed tumour (CABMT), solid carcinoma, malignant myoepithelioma, intraductal papillary carcinoma, comedocarcinoma and micropapillary invasive carcinoma. Among malignant tumours, 66.67-%, 23.81% and 9.52% tumours were assigned to low-grade, intermediate-grade and high-grade, respectively.